PENGEMBANGAN PRODUK FURNITURE RAMAH LINGKUNGAN BERBAHAN BAKU KAYU CEPAT TUMBUH PADA UMKM PENGOLAHAN KAYU UD. PUTRA MEUBELLER LOMBOK TENGAH - Fahrussiam, Fauzan; Pradityatama, Maharsa; Hidayanti, Anna Apriana (Jurnal Abdi Insani, 2024)
The sustainability of micro, small, and medium enterprises (MSMEs) in the woodcraft industry is increasingly challenged by competition from industrial-scale composite products. This market pressure has contributed to the ongoing decline of the partner enterprise, UD Putra Meubeller. The decline in this woodcraft business can be attributed to three primary factors: production, management, and marketing. This community engagement initiative focuses specifically on addressing the production-related issues. The engagement process is conducted through five stages: socialization, training, technology implementation, evaluation and assistance, and program sustainability. The knowledge gained by the partner during the training phase has introduced new ideas for product development in wood processing. The partner has acquired new insights related to yakisugi finishing techniques, raw material control from fast-growing wood species, and the maintenance of woodcraft machinery. This initiative is expected to reinvigorate the woodcraft business by refreshing product designs to align with current market trends and preferences in the furniture sector.